2011
DOI: 10.4143/crt.2011.43.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Expression of BamHI-A Rightward Transcripts in Epstein-Barr Virus-Associated Gastric Cancers

Abstract: PurposeAbout 10% of all gastric cancers (GCs) are Epstein-Barr virus (EBV)-associated. However, the oncogene of EBV in gastric carcinogenesis has not yet been established. In the present study, we investigated the virus-derived transcripts in the EBV-infected GC cell line to explore the viral oncogene of EBV-positive GCs.Materials and MethodsWe used the SNU719 cell line, a naturally derived EBV-infected GC cell line. The individual expressed sequence tags from the cDNA libraries of SNU719 were searched against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The magnitude of expression from the BamHI A region relative to the transcription levels of other EBV genes is striking, however. This result is consistent with a previous report using a naturally infected EBV positive gastric carcinoma cell line [26]. Nevertheless, our analysis makes this observation in the natural in vivo setting of the tumor, and the use of RNA-seq facilitated the evaluation of transcript structures and the magnitudes of BamHI A region gene expression relative to other viral and cellular genes.…”
Section: Discussionsupporting
confidence: 92%
“…The magnitude of expression from the BamHI A region relative to the transcription levels of other EBV genes is striking, however. This result is consistent with a previous report using a naturally infected EBV positive gastric carcinoma cell line [26]. Nevertheless, our analysis makes this observation in the natural in vivo setting of the tumor, and the use of RNA-seq facilitated the evaluation of transcript structures and the magnitudes of BamHI A region gene expression relative to other viral and cellular genes.…”
Section: Discussionsupporting
confidence: 92%
“…BNLF-2A , detected in a significant number of our cases, may protect infected B-cells from immune recognition and elimination[ 53 ]. Finally, the EBV transcriptome during the reactivation may involve the contribution of a wide array of other virus-encoded RNAs, such as BARF-0, BARF-1, BcLF-1, and RPMSI-1[ 54 ], that are not translated and may function as non-coding RNA molecules which could participate in regulating gene expression[ 55 ]. Heterogeneity in lytic/latent expression programs can be observed not only between patients but also within individual tumors, on a cell-to-cell basis.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, significant progress has occurred in the past decade in characterizing effects of EBV on host cell-encoded immunoregulatory microRNA [ 8 16 ] and also expression of viral-encoded noncoding and microRNA [ 17 26 ]. However, the author and others have previously suggested that much of the immunopathology associated with EBV infection may involve “hit-and-run” effects of EBV gene products transiently expressed in noninfected bystander cells [ 32 ].…”
Section: Ebv-encoded Microrna: a New Paradigm For Viral Immunopathmentioning
confidence: 99%
“…The author has also previously suggested that EBV may also potentially affect the biology bystander cells such as T lymphocytes through a variety of mechanisms in autoimmune syndromes such as systemic lupus erythematosus (SLE) which are related to EBV infection based on epidemiologic evidence [ 7 ]. Since numerous recent publications confirm that viral-encoded microRNA have a complex relationship with host-encoded immunoregulatory microRNA [ 8 16 ], and viral-encoded microRNA are themselves apparently coregulated by host and viral immune response transcription factors [ 17 26 ], it is reasonable to include viral and host microRNA in the “shared gene paradigm.”…”
Section: Introduction: Overview Of Ebv Pathogenesis In Autoimmune mentioning
confidence: 99%